2011
DOI: 10.1002/emmm.201100131
|View full text |Cite
|
Sign up to set email alerts
|

Non‐canonical functions of the tuberous sclerosis complex‐Rheb signalling axis

Abstract: The protein products of the tuberous sclerosis complex (TSC) genes, TSC1 and TSC2, form a complex, which inhibits the small G-protein, Ras homolog enriched in brain (Rheb). The vast majority of research regarding these proteins has focused on mammalian Target of Rapamycin (mTOR), a target of Rheb. Here, we propose that there are clinically relevant functions and targets of TSC1, TSC2 and Rheb, which are independent of mTOR. We present evidence that such non-canonical functions of the TSC-Rheb signalling networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 103 publications
5
75
0
Order By: Relevance
“…We previously found that suppression of Rheb-GTPase activity with farnesyl transferase inhibitors almost completely rescued spine synapse formation 14 . Thus, a non-canonical pathway such as this Rheb-syntenin signalling may participate in some of the symptomatic manifestations in TSC [40][41][42] . Indeed, knockdown and knockout of brain syntenin restored contextual fear discrimination deficits in Tsc2 þ / À rats and mice, respectively (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that suppression of Rheb-GTPase activity with farnesyl transferase inhibitors almost completely rescued spine synapse formation 14 . Thus, a non-canonical pathway such as this Rheb-syntenin signalling may participate in some of the symptomatic manifestations in TSC [40][41][42] . Indeed, knockdown and knockout of brain syntenin restored contextual fear discrimination deficits in Tsc2 þ / À rats and mice, respectively (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…TSC1 and TSC2 mutations are responsible for tuberous sclerosis and are associated with other diseases including pulmonary lymphangioleiomyomatosis 23 . 3D structures of TSC1, TSC2 and their complex are crucial for understanding their normal function and regulation and the pathogenic mechanism of their mutations.…”
Section: Discussionmentioning
confidence: 99%
“…TSC1 protein has many binding partners in addition to TSC2, and is essential for mouse embryonic development [22][23][24] . Recently, it has been shown that TSC1 has critical roles in neurodevelopment and neurological diseases, immune diseases, diabetes, autophagy and DNA repair [25][26][27][28] .…”
mentioning
confidence: 99%
“…Recently, several signaling pathways of TSC complex and Rheb have been described that function independently of mTORC1 (Jacinto et al, 2004;Karbowniczek et al, 2006;Zhou et al, 2009;Neuman and Henske, 2011). Hence, the activation of these non-canonical pathways cause some of the clinical manifestations of TSC that are resistant to mTORC1 inhibition by rapamycin (Yasuda et al, 2014).…”
Section: Non-canonical Rheb Pathwaymentioning
confidence: 99%